Comparison of efficiency between RMI1 and RMI2 in diagnosing ovarian malignancy - Shalagar, Rashmi R.; Kabadi, Narayan Y. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: This study was conducted in department of obstetrics and gynaecology, to know the efficiency of risk of malignancy index (RMI) to differentiate a malignant from a benign tumor and to compare the efficiency of risk of malignancy index 1 and 2 (RMI1 and RMI2). The study was conducted from June 2012 to August 2013 in women who got admitted with adnexal tumor. Methods: It was a prospective study. A proforma was designed for each patient which included, name, age, complaints, menopausal status, parity, past and family history and associated medical condition were asked. Indivisual parameters namely ultrasound score, CA125 and menopausal status and risk of malignancy index was calculated and compared with final histopathological diagnosis and sensitivity specificity and positive predictive value was calculated for each. Results: : The sensitivity of RMI1 is 87.95%, specificity is 75%, positive predictive value is 94.8%, negative predictive value is 54.54%, percentage of false negative is 12.04% and percentage of false positive is 25%. The sensitivity of RMI2 is 86.74%, specificity is 81.25%, positive predictive value is 96%, negative predictive value is 54.16%, percentage of false negative is 13.25% and percentage of false positive is 18.75%. Conclusions: The efficiency of RMI was definitely better than indivisual parameters and efficiency of RMI 1 and RMI2 are similar.